Stand Fast, Craig-Royston! (Volume III) - Black, William, 1841-1898 (Salt Lake City, UT : Project Gutenberg, 2013)
"Stand Fast, Craig-Royston!" by William Black is a novel written in the late 19th century. The story follows Vincent Harris, a young man in search of George Bethune and his granddaughter, Maisrie, who have mysteriously disappeared. Set against a backdrop that blends elements of love, social intrigue, and self-discovery, the narrative explores themes of honor, loyalty, and the complexities of human relationships. The opening of the novel introduces Vincent as he anxiously seeks information about George Bethune from Courtnay Fox, a journalist. Their conversation reveals Vincent's deep concern for Maisrie and her grandfather, which intensifies when he learns of negative rumors circulating about them. This unsettling encounter fuels Vincent's determination to find them, leading him on a quest that traverses settings from London to America. As he navigates various obstacles, including social prejudice and misunderstandings, the stage is set for a profound exploration of love and resilience amidst external challenges. (This is an automatically generated summary.)
Release date is 2013-05-17
Produced by Al Haines
Keywords: Grandfathers -- Fiction; Scotland -- Social life and customs -- 19th century -- Fiction; Families -- Fiction; Older people -- Fiction